La Huerta de don Marcos - De Paz, Amelia (El Colegio de México, 2012)
The Huerta de don Marcos, near Cordova, is one of the places associatedwith Góngora, because it is believed that the poet wrote his major worksthere. This paper examines the origin and causes of that idea, and the rolethat the Huerta played in Góngora’s life.